Effects of Modifiable Footwear Features on Anterior Cruciate Ligament Force in Young Females during a Drop-Lateral-Jump Task. - CHI, PEI-WEI; PATERSON, KADE L.; HINMAN, RANA S.; WU, WEN; MCNAMARA, STELLA; MANIAR, NIRAV; AKHUNDOV, RIAD; SAXBY, DAVID J.; NASSERI, AZADEH; BRYANT, ADAM L. (Medicine & Science in Sports & Exercise, 2026)
Purpose: Aberrant lower limb biomechanics of young females contribute to elevated knee loads and a susceptibility to noncontact anterior cruciate ligament (ACL) injury. Specific design features of athletic footwear may alter impact-related loads transferred up the kinetic chain to the knee. This cross-sectional biomechanical study examined the effects of modifiable footwear design features (heel height/pitch and medial arch support) on ACL force-time parameters of females during single-limb landing. Methods: Fifty-two healthy late/postpubertal females (Tanner stage IV–V) performed a single-limb drop-lateral-jump task in nine footwear conditions, with different combinations of shoe pitch (4, 7, and 10 mm) and medial arch support (no support, low support, and high support). Using three-dimensional joint kinematics, ground-reaction forces, and electromyography data, an electromyography-informed neuromusculoskeletal computational model predicted ACL force during the weight-acceptance phase of the drop-lateral-jump task. A mixed-effects linear regression model was used to compare the magnitude and temporal characteristics of ACL force between footwear conditions. Tukey's post hoc comparisons were conducted for significant (P < 0.05) main effects or interactions. Results: For peak ACL force, no significant main effect or interaction was found. A significant main effect of shoe pitch was found for time-to-peak ACL force (P < 0.001), where the 4-mm shoe pitch delayed time-to-peak by 3.23 and 4.28 ms compared with the 7 mm (P < 0.001) and 10 mm (P < 0.001) conditions, respectively. Conclusions: Although a delayed time-to-peak ACL force was observed with the 4-mm shoe pitch condition, the relatively small temporal differences observed, and the fact that peak ACL force did not differ across pitch variants, suggest that these findings may have few real-world implications.